DELIVERY OF MATERIALS REQUIRED FOR THE MAINTENANCE AND REPAIR OF PAVED ROADS IN THE CENTRAL AREA OF THE KINGDOM OF POLAND AFTER THE FALL OF THE NOVEMBER UPRISING - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The article explores the stress-strain state of the pneumatic flexible shaft coupling of the tumbling mill drive using a software of finite element analysis. The study has revealed that the stress-strain state of the pneumatic flexible shaft coupling is characterized by an uneven general and local distribution of stresses. Areas of maximum stress and strain in the pneumatic flexible shaft coupling have been defined. The study allowed for changing the geometry and reducing the mass of the disc of the pneumatic flexible shaft coupling with a slight change in stresses and strains. The results of the study can be applied to the design of pneumatic flexible shaft couplings and serve as a basis for further research.